From India to Israel : identity, immigration and the struggle for religious equality - Hodes, Joseph, 1976- (McGill-Queen's studies in the history of religion., 2014)
Between May 1948 and December 1951, Israel received approximately 684,000 immigrants from across the globe. This book examines Israel's first decades through the perspective of an Indian Jewish community, the Bene Israel, who would go on to play an important role in the creation of the state.